Unusual Presentation of Endometriosis - Ajit Mahale; Nina Mahale; Santosh Kondapalli (Asian Journal of Medical Research, 2013)
We report a case of 36 year old female with complaints of low backache and pain radiating to left lower limb since 2 months and correlate the MRI findings with the operative and histopathological findings. The lesions appeared as lobulated and multicystic in the pelvis midline extending upto the lower abdomen with few solid components in the right adnexa and septated mass in the left adnexa. The masses were found to show hyperintensity on T1 weighted images, FAT SAT images and hypo to isointense on T2 weighted images. But the lesion in the left adnexa was suppressed on the FAT SAT images suggesting the strong possibility of dermoid. All these structures were confirmed by histopathology to correspond with presumptive endometriosis of left ovary and simple serous cysts of right ovary.